Head stabilization apparatus for high-resolution ophthalmic imaging - Vienola, Kari V.; Holmes, John A.; Glasso, Zolten; Rossi, Ethan A. (Optica, 2025)
Head movement must be stabilized to enable high-quality data collection from optical instrumentation such as eye trackers and ophthalmic imaging devices. Though critically important for imaging, head stabilization is often an afterthought in the design of advanced ophthalmic imaging systems, and experimental devices often adapt used and/or discarded equipment from clinical devices for this purpose. Alternatively, those seeking the most stable solution possible, including many users of adaptive optics ophthalmoscopy systems, utilize bite bars. Bite bars can provide excellent stability but are time consuming to fabricate, decreasing imaging efficiency, and uncomfortable for many patients, especially the elderly and/or those with prosthodontics such as dentures who may refuse participation in a study that requires one. No commercial vendors specifically offer head mount solutions for experimental ophthalmic imaging devices, resulting in nearly every custom device having a different solution for this commonly encountered problem. Parallelizing the head stabilization apparatus across different custom devices may improve standardization of experimental imaging systems for clinical trials and other multicenter investigations. Here we introduce a head mount design for ophthalmic imaging that is modular, adjustable, and customizable to the constraints of different experimental imaging configurations. The three points of head contact in our solution provide excellent stabilization across a range of head sizes and shapes from small children to adults, and the ease of adjustment afforded by our design minimizes the time to get participants stabilized and comfortable.